Reconciling food and water security objectives of MENA and sub-Saharan Africa: is there a role for large-scale agricultural investments? - Williams, Timothy O. (Springer, 2015)
The attainment of food and water security rank high on the agendas of governments in the Middle East and North Africa (MENA) region and sub-Saharan Africa (SSA). Although the objectives are similar, the underlying drivers, resource endowments and opportunities for achieving them are different. Differences between two regions in natural resource endowment and investment capital stock can, in theory, lead to mutually beneficial trade to achieve desired objectives. Concerns about the recent food crises coupled with the disparity in land and water endowment and investable capital between MENA and SSA have led in recent years to investment in agricultural land in the latter by a number of MENA countries with the aim of producing food. At the same time, many SSA countries seek these investments to infuse capital, technology and know-how into their agricultural sector to improve productivity, food security and rural livelihoods. However, these recent foreign direct agricultural investments have to date performed poorly or have been abandoned without achieving the initial objectives of setting them up. Based on research conducted in selected sub-Saharan countries, this paper analyses the reasons for the failure of these investments. It then reviews a few successful agricultural investments by private sector companies with a long history of operation in SSA. Juxtaposing lessons distilled from failed and successful case studies, the paper argues that large-scale agricultural investments that take advantage of this accumulated knowledge are needed and do have a critical role to play. Such investments, when they also incorporate ecosystems management practices and smallholder inclusive business models in their operations, can serve as appropriate instruments to reconcile the food and water security objectives of both the MENA region and SSA, while promoting sustainable intensification of agriculture and improved rural livelihoods in SSA.